PREFERENSI PEDAGANG PASAR TRADISIONAL DALAM MEMILIH JASA MODAL USAHA PADA LEMBAGA KEUANGAN DI MASA PANDEMI COVID-19 - Sugeng Nugroho (At-Tauzi : Jurnal Ekonomi Islam, 2021)
This study aims to find the factors that influence Traditional Market Traders – as a potential market for Financial Institutions, in choosing credit or financing products for business capital development during the covid-19 pandemic. This study tries to rule out the existence of a social capital network for the covid-19 pandemic.This study uses a quantitative data approach that was collected from a number of 100 respondents using a 5 Likert scale questionnaire. The sampling technique used non-probability quota sampling, with a total of 14 questionnaire items (dimensions). The analysis technique using Multi Dimension Scaling (MDS) with the help of SPSS Version 25 found five factors that influence the decision to choose business capital products from financial institutions, namely: the people factor (sympathetic and familiar officers); process factor (administration and easy/fast disbursement); empathy factor (loan funds are greater than the value of the collateral); factor product (many customers who take); and price factor (low interest rate/profit sharing)